Damaged fragments of an amalaka - Temples of India Project Team (Jio Institute, 2024)
Damaged fragments of amalaka, now kept along the south boundary wall with other broken fragments recovered from the debris of the original temple. The amalaka is a ribbed disk-shaped stone, symbolic of the lotus and placed on the highest point of the shikhara (spire). The amalaka is crowned by a kalasam (sacred pot). Several amalakas have been recovered at the site.